"Migrant network : help or hindrance?" : the case of Indonesian student migrants in Singapore - Tander, Clarissa (2015)
This research examines the role of migrant network in international student migration and extends prior studies on migrant network theory that cover mainly of migrant workers. Using in-depth semi-structured interview of Indonesian private university students studying in Singapore, I explore the role of migrant networks and it’s significance in the outflow of Indonesian students into Singapore. Findings showed that migrant network plays an instrumental role in motivating migration, and this is especially true for family members of potential migrants. Migrant networks play a dual role in a student migrant’s assimilation process whilst living overseas. The strong presence of a migrant community could both help and hinder student migrants’ assimilation to the culture in the migrant-receiving country but its effects vary between migrants. This non-uniformity between assimilation outcomes is moderated by individual attitudes and personal reasons for migration. Finally, availability of migrant network support influences student migrants’ future outlook upon graduation to a large extent, impacting migrants’ decision to stay or return.